2008
DOI: 10.1007/s00408-008-9073-y
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Endothelial Cells and Endothelial Progenitor Cells in Obstructive Sleep Apnea

Abstract: Increased circulating endothelial cells (CECs) have been observed in patients with vascular injury associated with acute myocardial infarction, pulmonary hypertension, and congestive heart failure. Decreased circulating endothelial progenitor cells (EPCs) have been observed in patients with risk factors for cardiovascular disease. Obstructive sleep apnea (OSA) is associated with increased risk of cardiovascular disease and endothelial dysfunction. Subjects were recruited from patients referred for overnight po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 29 publications
3
39
0
1
Order By: Relevance
“…The number of apoptotic endothelial cells in the circulation was lowered by therapy with nasal CPAP. However, contrasting results were reported in another recent study [92].…”
Section: Clinical Studiesmentioning
confidence: 56%
See 1 more Smart Citation
“…The number of apoptotic endothelial cells in the circulation was lowered by therapy with nasal CPAP. However, contrasting results were reported in another recent study [92].…”
Section: Clinical Studiesmentioning
confidence: 56%
“…While lower numbers of EPCs have been noted in OSAS patients [93,94], one study has shown no statistical difference in either circulating endothelial cells or circulating EPCs in a group of OSAS patients, free of preexisting vascular disease, compared with age-and weightmatched controls [92].…”
Section: Clinical Studiesmentioning
confidence: 98%
“…Lung homogenates were incubated with platelet-endothelial cell adhesion molecule (PECAM, CD31)-conjugated magnetic beads, and immunocomplexes were separated from homogenate with a magnetic column (25) and seeded on culture dishes in medium for 24 h. Cells were collected, and lysates were used for immunoblot analysis.…”
mentioning
confidence: 99%
“…[11][12][13][14][15][16][17] Although they generally show abnormalities in the different aspects of endothelial function in OSA, the results show substantial variability, often with controversial findings. [11][12][13][14][15][16][17][18][19][20] This may be because of the concomitant confounding factors known to influence endothelial function independent of OSA. Also, myocardial blood flow reserve (MBFR) is a well-validated surrogate marker of coronary perfusion and provides an estimation of coronary flow reserve.…”
mentioning
confidence: 99%